Tensile strength and porosity of regolith-based cement with human hair - Tarikuzzaman, Mohammad; Shank, Audrey M.; Agan, Emma G.; Sagar, Viral; Lynam, Joan G.; Gordon Ⅱ, Stephen T.; Alam, Shaurav (Frontiers in Space Technologies, 2024)
Sustainable structures are an important area of research, particularly for anticipated extended human presence on the Moon or Mars. Persistent human presence on the Moon will require building materials that are already present at the site to construct bases. The high cost associated with reinforcing metal (rebar) in mission payloads necessitates the exploration of alternative reinforcement methods for sustained lunar bases. Human hair is strong in tensile strength and will become available in any long-term mission. By using otherwise wasted hair instead of heavy metal, mission payloads and costs could be lowered. Concrete workability, compressive strength, and porosity were measured for a series of different cement compositions. These compositions consisted of combinations of Ordinary Portland Cement (OPC), lunar regolith, deionized (DI) water and human hair. Increased workability and porosity were found for increasing hair concentrations. Compressive strength slightly decreased with increased hair concentration.